Epidemiology of HEV in the Mediterranean basin: 10-year prevalence in Italy. Issue 7 (14th July 2015) - Lanini, Simone; Garbuglia, Anna Rosa; Lapa, Daniele; Puro, Vincenzo; Navarra, Assunta; Pergola, Catia; Ippolito, Giuseppe; Capobianchi, Maria Rosaria
Abstract : Objectives: The present study is aimed at describing the seroprevalence and exploring potential risk factor(s) for hepatitis E virus (HEV) in participants who voluntarily underwent anti-HIV antibody testing. Study design: Seroprevalence study. Setting: The HIV prevention unit at the National Institute for Infectious Diseases Lazzaro Spallanzani, serving as a referral centre for HIV infection in Lazio, an Italian Region with about 5.6 million inhabitants. Participants: Participants are a random sample of all subjects who receive counselling and undergo serological tests for anti-HIV antibody (Ab) between 2002 and 2011. Risk factors and outcome: A set of 16 epidemiological variables (risk factors) were assessed for association with positivity to anti-HEV IgG (outcome). Results: Between 2002 and 2011, 27 351 serum specimens and related epidemiological information were collected; of these 1116 were randomly selected and analysed. The overall anti-HEV IgG prevalence was 5.38% (60 out of 1116) with evidence of potential heterogeneity between years of sampling (p=0.055). Multivariate analysis provided evidence that anti-HEV IgG prevalence increases by 4% per year of participants' age (95% CI 1% to 7%, p=0.002). In addition, men who have sex with men and participants who were born outside Italy have an OR for past HEV infection that is about two times higher than in those who were not (p=0.040 and p=0.027, respectively). Analysis of temporal trend showed that variation of anti-HEV IgG can be well explained by a cubic logistic regression model, which describes the variation of prevalence over time as a fluctuation within a 3-year period (p=0.032). Conclusions: This study provides new evidence that besides the orofecal and zoonotic routes, intimate contacts between males may be a significant mode of HEV transmission.